O DIÁLOGO ENTRE A GEOGRAFIA HUMANA DE MILTON SANTOS E A COMUNICAÇÃO SOCIAL - RAMALHO, LUIZ FERNANDO (2016)
This thesis is a theoretical work that is supported, in one hand, on the work of the Brazilian intellectual Milton Santos in the field of Human Geography, and in the other on contemporary social communication, as the basis for an analysis that attempted to identify the interfaces between the two areas. Throughout the text, we attempted to point out the author's contributions to the field of social communication, especially considering the new digital media and the present intermediated communication that happens in computer devices, digital bases and connected by global networks. The text discusses the main ideas presented by Santos as the ontology of space, object systems, systems of action, technical systems, the uniqueness of the technique, time and engine, outlining what the author will call technical-scientific-informational. The work suggested points of connection between the themes cited theoretical thoughts and practical examples coming from communication, in a dialectical approach and interdisciplinary perspective, exchanging knowledge in order to understand what is the influence of communication on the creation of geographical space.